FRI0650-HPR SEXUAL DYSFUNCTION IN WOMEN WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Espasa, G. V.; Gonzalez Lucero, L.; Soria Curi, Y.; Barbaglia, A. L.; Mazza, S. M.; Leguizamón, M. L.; Pera, M.; Sueldo, H. R.; Bertolaccini, M. C.; Santana, M.; Galindo, L. M.; Bellomio, V. I.
Abstract : Background: Sexual dysfunction is the alteration in one or several phases of sexual activity (desire, excitement, plateau, orgasm and resolution), which can culminate in frustration, pain and a decrease in the frequency of sexual intercourse. There are few studies that associate sexual dysfunction with Systemic Lupus Erythematosus (SLE) due to the difficulty in assessing it and its multifactorial cause. Objectives: Determine the frequency of sexual dysfunction and analyze associated factors in patients with SLE. Methods: A descriptive cross-sectional study was conducted. We included patients who attended the Rheumatology unit between May and July 2019; over 18 years of age, with a diagnosis of SLE according to the ACR 1997 and / or SLICC 2012 criteria, and healthy patients matched by age as control. Demographic and disease-related variables were studied. The DASS-21 (Depression Anxiety Stress Scale) scale that evaluates depression, anxiety and stress, and the Female Sexual Function Index (FSFI) that assesses 6 domains (desire, excitement, lubrication, orgasms, satisfaction and pain) were applied with a cut-off point ≤ 26.5 to define sexual dysfunction. Women over 50 years old, with secondary Sjogren's syndrome, menopause, severe depression and illiterate patients were excluded. Results: One hundred and twenty three women were included (60 with SLE and 63 controls), with a mean age of 34.3 ± 8.3 and 31.7 ± 4.4 years respectively. The prevalence of sexual dysfunction in the SLE group was 71.7%; 95% CI = [58.5 – 82.5], and 23.8%, 95% CI = [13.9 – 36.2] in healthy patients. There were significant differences in all domains of sexual function between women with SLE and healthy group. In the desire, excitement and pain domains the differences were notable. The total FSFI score in patients with SLE was 18.2 ± 11.2 and in healthy women 28.3 ± 6.9 (p=0.001). Stress, anxiety and depression were observed in 58.4%, 58.3% and 50% of women with SLE and 19%, 20.6% and 28.5% of healthy women respectively (p=0.001). No association was found between sexual dysfunction and age, age at diagnosis, disease activity or treatment (pNS). No association was found in patients with SLE when analyzing the effect of sexual dysfunction in stress, depression and anxiety variables, in opposition to the healthy group (p<0.05). Conclusion: The prevalence of sexual dysfunction in patients with SLE was high (71.7%). Depression, Anxiety, and Stress were not decisive variables in Sexual Dysfunction. Disclosure of Interests: None declared